2014
DOI: 10.2215/cjn.02560314
|View full text |Cite
|
Sign up to set email alerts
|

Nephron Hypertrophy and Glomerulosclerosis and Their Association with Kidney Function and Risk Factors among Living Kidney Donors

Abstract: Background and objectives The relationship of kidney function and CKD risk factors to structural changes in the renal parenchyma of normal adults is unclear. This study assessed whether nephron hypertrophy and nephrosclerosis had similar or different associations with kidney function and risk factors.Design, setting, participants, & measurements From 1999 to 2009, 1395 living kidney donors had a core needle biopsy of their donated kidney during transplant surgery. The mean nonsclerotic glomerular volume and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 51 publications
4
96
3
3
Order By: Relevance
“…Low nephron count in humans has previously been associated with tubular hypertrophy (43). In response to the increased filtered load, compensatory cellular hypertrophy in proximal tubules increases Na + reabsorption, which restores NaCl delivery to distal tubules via tubuloglomerular feedback (44).…”
Section: Discussionmentioning
confidence: 99%
“…Low nephron count in humans has previously been associated with tubular hypertrophy (43). In response to the increased filtered load, compensatory cellular hypertrophy in proximal tubules increases Na + reabsorption, which restores NaCl delivery to distal tubules via tubuloglomerular feedback (44).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed anatomic and physiologic studies of the healthiest of the healthy, normal living donors for kidney transplantation by the Mayo Clinic and Cleveland Clinic have been particularly revealing. [14][15][16][17][18][19] We are all born with a complement of nephrons determined in large part by the process of nephrogenesis in utero. 20 This process can be influenced, either negatively or positively by the maternal-fetal nexus.…”
Section: What Is the Aging Kidney?mentioning
confidence: 99%
“…19 However, albuminuria does highly correlate with glomerular enlargement, the latter of which may be a manifestation of nephron endowment rather than nephron loss with aging. 14 Disentangling the different effects of low nephron endowment and the physiologic loss of nephrons with aging will required additional study.…”
Section: What Is the Aging Kidney?mentioning
confidence: 99%
“…In living donors, the prevalence of glomerulo-nephrosclerosis increases linearly with age from 2.7 % for donors aged 18-29 years, to 73 % for donors aged 70-77 years [45]. Elsherbiny et al found correlations between some donor characteristics with structural changes in the renal parenchyma [46]. Male sex, high kidney function, albuminuria, family history of renal disease, and high BMI were independently associated with features of nephron hypertrophy (large glomerular volume, large tubular area, and low nonsclerotic glomerular density).…”
Section: Kidney Histology In Living Donorsmentioning
confidence: 99%